Gold Doping of Silver Nanoclusters: A 26‐Fold Enhancement in the Luminescence Quantum Yield. Issue 19 (6th April 2016) - Soldan, Giada; Aljuhani, Maha A.; Bootharaju, Megalamane S.; AbdulHalim, Lina G.; Parida, Manas R.; Emwas, Abdul‐Hamid; Mohammed, Omar F.; Bakr, Osman M.
Abstract: A high quantum yield (QY) of photoluminescence (PL) in nanomaterials is necessary for a wide range of applications. Unfortunately, the weak PL and moderate stability of atomically precise silver nanoclusters (NCs) suppress their utility. Herein, we accomplished a ≥26‐fold PL QY enhancement of the Ag29 (BDT)12 (TPP)4 cluster (BDT: 1, 3‐benzenedithiol; TPP: triphenylphosphine) by doping with a discrete number of Au atoms, producing Ag29− x Au x (BDT)12 (TPP)4, x =1–5. The Au‐doped clusters exhibit an enhanced stability and an intense red emission around 660 nm. Single‐crystal XRD, mass spectrometry, optical, and NMR spectroscopy shed light on the PL enhancement mechanism and the probable locations of the Au dopants within the cluster. Abstract : The photoluminescence quantum yield (QY) of a weakly luminescent Ag29 nanocluster was 26‐fold enhanced by doping the nanocluster with a distinct number of gold atoms, while the original Ag29 framework was kept intact. A detailed characterization showed the presence of Au heteroatoms replacing the silver atom at the center of the Ag29 nanocluster and the atoms at the four phosphine binding sites of Ag29, which play a pivotal role in the QY enhancement mechanism.